On the role of anisotropy of membrane constituents on the elastic properties of highly curved lipid membranes - Perutková, Šárka (visokošolska dela, 2017)
The primary objective of the thesis covers in the theoretical study the role of anisotropic membrane components in the elasticity of highly curved biological membranes. To show the importance of anisotropy, we focused on one type of non-lamellar membrane self-assembly - the inverted hexagonal phase and the membrane tubular protrusions with attached proteins. These two structures represent excellent examples of highly curved structures in which the anisotropy of molecules or small domains plays an important role. In the first part of the thesis, we developed a theoretical model describing the stability of the inverted hexagonal phase, which considers lipid anisotropy and deviations from the circularity of the pivotal plane cross-section. We applied a wedge-like model of phospholipid molecules, in which the phospholipid molecule is described as a wedge, with the angle of the wedge increasing with temperature. However, we also took into account the average orientation of lipids by including the deviatoric bending energy contribution derived from statistical physics. Theoretical predictions of our model showed that a crosssection of the inverted hexagonal phase is an intermediate between a circle and a hexagon, and that it has lower energy than the circular cross-section. The results were in agreement with observations gathered by the small angle X-ray scattering. By comparing our results with the experiments, we predicted some values of the mean intrinsic curvature and the phospholipid chain stiffness. In the second part of the thesis, we developed a theoretical model, which describes the stabilisation of membrane nanotubes containing attached anisotropic flexible rod-like proteins. We derived the free energy of a vesicle with nanotube taking into account the rotational averaging of the anisotropic attached proteins. We also added the entropy contribution due to the non-homogeneous lateral distribution of proteins. Our theoretical results showed that rod-like attached proteins and membrane domains can stabilise the membrane tubular protrusions if we consider the protein/domain anisotropy. Our results were also in agreement with experimental results in which isotropic membrane constituents were found on the tips of the nanotube or on the mother vesicle; however, the anisotropic membrane constituents were detected along the nanotubes. Our results showed that rod-like attached proteins and membrane domains can stabilise the membrane tubular protrusions if we consider the protein/domain anisotropy. The anisotropy of membrane constituents can lower the membrane free energy in regions of high curvature. The main aim of the thesis was to show that the anisotropy of membrane constituents can lower the membrane free energy in regions of high curvature and that the rotational averaging of anisotropic membrane components should be considered in the evaluation of the membrane free energy at highly curved membrane structures.
Keywords: Biološke membrane; biomembranes; Disertacije; dissertations; inverted hexagonal phase; invertna heksagonalna faza; lipid anisotropy; lipidna anizotropija; membrane nanotubes; membrane protein sorting; membranske nanocevke; paličasti proteini; rod-like proteins; rotacijsko povprečje; rotational averaging; sortiranje membranskih proteinov